Pengaruh Kombinasi Ekstrak Daun Pepaya (Carica Papaya) dan Daun Jambu Air (Syzgium Aqueum) terhadap Daya Hambat Pertumbuhan Escherichia Coli ATCC 25922: Penelitian - Sri Sela Pratiwi; Sonja Verra Tinneke Lumowa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Using the well diffusion method, papaya (Carica papaya L.) and water guava (Syzygium aqueum) leaf extracts were investigated for their capacity to inhibit Escherichia coli ATCC 25922. Samples came from North Samarinda's Paperta, Jalan Grogot, and Perjuangan neighborhoods. 96% ethanol was used for the extraction process, which was then blended in five different concentrations and repeated four times. The existence of alkaloids, flavonoids, tannins, saponins, steroids, and phenolics was demonstrated by the phytochemical data. With the exception of the positive control chloramphenicol, which had an average of 24.7 mm, the antibacterial test did not reveal an inhibitory zone at different concentrations.